2023
DOI: 10.3390/cancers15020436
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Outcome of Laparoscopic Microwave Ablation for Hepatocellular Carcinoma

Abstract: In the context of spreading interest in textbook outcome (TO) evaluation in different fields, we aimed to investigate an uncharted procedure, that is, laparoscopic microwave ablation (MWA) for hepatocellular carcinoma (HCC). Absence of post-MWA complications, a hospital stay of three days, no mortality nor readmission within 30 days, and complete response of the target lesion at post-MWA CT scan defined TO achievement. Patients treated between January 2014 and March 2021 were retrospectively reviewed, and of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, an Italian study reported that when textbook outcomes are reached, LA may indeed prove to be a curative therapy [ 69 ]. The same study group conducted a large multicenter study (as yet unpublished), comparing three cohorts of patients undergoing pRFA, laparoscopic microwave ablation (LA), or TACE.…”
Section: Does Mils Expand the Indications For Hcc Ablation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an Italian study reported that when textbook outcomes are reached, LA may indeed prove to be a curative therapy [ 69 ]. The same study group conducted a large multicenter study (as yet unpublished), comparing three cohorts of patients undergoing pRFA, laparoscopic microwave ablation (LA), or TACE.…”
Section: Does Mils Expand the Indications For Hcc Ablation?mentioning
confidence: 99%
“…Finally, tumor ablation using LA is considered hierarchically superior to TACE, so before deciding to use intra-arterial therapy, the feasibility of LA should be considered [ 68 , 69 ]. This novel operative framework is fashioned to assist the decision-making of experts in the setting of a multidisciplinary meeting.…”
Section: What Is the Role/position Of Mils In The Hcc Treatment Algor...mentioning
confidence: 99%